Perception of telemedicine among orthopedic surgeons and patients and an analysis of the factors governing its overall efficacy: Results from the COVID-19 pandemic - Sumit Banerjee; Jeshwanth Netaji; Akshat Gupta; Nitesh Gahlot; Nilesh Barwar; Abhay Elhence (Wolters Kluwer Medknow Publications, 2023)
Background: Providing health-care services through telemedicine for musculoskeletal ailments after the first wave of COVID-19 may help reduce the burden on the already-strained health-care system. Objectives: The objectives of this study were (1) to assess the satisfaction levels of orthopedic surgeons and patients with respect to telemedicine and (2) to determine the factors governing the overall efficacy of telemedicine consultations. Materials and Methods: A cross-sectional study was conducted to ascertain the perception of telemedicine (both doctors and patients) under the following domains - (1) information provided and ease of usage; (2) doctor-patient communication; (3) ease of prescribing and understanding treatment; and (4) audio-video quality of the consultation. The influence of these factors on overall satisfaction was determined using multinomial logistic regression analysis. Results: Of the 204 patients and 27 surgeons who completed the questionnaire, 77% (patients) and 89% (surgeons) were satisfied with the overall efficacy of telemedicine. Maximum satisfaction was noted with the ease of obtaining a telemedicine appointment (168/204). 68.6% of patients further stated they would prefer future visits virtually. While all four factors were found to have a significant correlation (P < 0.001) with the overall efficacy of teleconsultation services, the quality of the telephone call (odds ratio [OR] =90.15) and good doctor-patient communication (OR = 15.5) were found to be the most important of the lot. Conclusion: Our study not only demonstrates the high degree of satisfaction with telehealth services but is also able to pinpoint the areas where improvement is needed to enhance the overall experience with this technology.